O discurso do progresso e os impactos das políticas de desenvolvimento nacional para os povos indígenas no Brasil: o legado da ditadura militar em e para além da usina hidrelétrica de Belo Monte - Taroco, Lara Santos Zangerolame (2018)
This dissertation analyzes the impacts of the national development polices of the military dictatorship established in Brazil in 1964 for indigenous peoples and for the current policies of national development whose democratic limits and guarantee of fundamental rights are foreseen by the Constitution. The case of the Belo Monte Hydroelectric Power Plant is taken as a prime example, because it is an enterprise inserted in several judicial controversies and, above all, because it was conceived during the Brazilian military dictatorship period. This case is understood as adequate to demonstrate, from a historical perspective, the effects of the development policies based on the discourse of progress for the democratic constitutionalism, proposed by the current Constitution, as well as the impacts for the indigenous peoples in the past and the present time. The analysis of this problematic is made on the basis of criticism of modernity, from the philosophical categories offered by Walter Benjamin and Giorgio Agamben and by the provocations raised by Marshall Berman, from Goethe's Faust. The dialogue between these authors is focused on the critique of modernity, highlighting the contributions of literature as an essential resource for a better understanding of the challenges imposed by the Brazilian context. Therefore, the concepts of "development," "progress," and "people" are analyzed in the light of Benjamin's critique of progressive historiography and Agamben's problematization of "biopolitics." From these bases and through historically contextualized analysis of the National Integration Program (NDP) and the II National Development Plan (NDP), this dissertation notes that there are still connections between the current development policies and the progressive discourse of the military dictatorship. It is argued that this approach also runs through the post-Constitution period of 1988, through the maintenance of projects such as the Belo Monte Hydroelectric Plant, which are located in a larger projection, demonstrate that violations of the rights of indigenous peoples occurred in this case , are also identified in other hydroelectric projects of the present day. Thus, it is necessary to rethink this model, in order to effectively consider the autonomy of indigenous peoples to direct the course of their development, in compliance with the constitutional text and Convention n. 169 of the International Labor Organization (ILO). In order to do so, it is necessary to take seriously the Brazilian constitutional past, considering the effects that it radiates to the present, in which the 1988 Constitution presents, above all, as a project of Democratic State of Right, to be in the face of inflows and unfulfilled promises from previous times, which is why the implications of this historical context can not be disregarded.